Study of electronystagmography in the diagnosis and efficacy of follow-up after treatment, in patients with vertigo of peripheral origin - ., Zorengpuii; Khiangte, Lalnuntluangi; P., Naveen (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Vertigo is a symptom of multisystemic disorders of various etiological factors with different clinical manifestations. The disorders causing the symptom may be of peripheral or central origin, and accurate diagnosis of the underlying pathology is warranted for effective treatment. Balance is a complex sensorimotor task involving accurate and redundant sensory input from the visual, vestibular and proprioceptive systems, central nervous system integration of the sensory signals and the generation of the appropriate motor commands and adequate musculoskeletal capabilities to perform the motor tasks involved in occulomotor and posture control. Methods: The study was conducted in the Department of Otorhinolaryngology, Regional Institute of Medical Sciences, Imphal, Manipur. 50 cases presenting with symptoms of vertigo were studied irrespective of age, sex and duration of illness in order to find out the cause of peripheral vertigo by using different diagnostic parameters with main emphasis on electronystagmography. All patients underwent pure tone audiometry for audiology assessment. The cases were treated and followed-up to a minimum period of 3 months, electronystagmography repeated during each visit to evaluate the efficacy and response to treatment. Results: Vertigo of peripheral origin comprised of 64%. Meniere’s disease was the largest group (28%) amongst the causes of peripheral vertigo. Subjective improvement of vertigo and electronystagmography was observed in all patients after treatment. Conclusions: Vertigo was most common in fourth decade of life and males have a slight predominance. Medical management was the mainstay of treatment. Patients with peripheral vertigo responded well to symptomatic and supportive treatment. Electronystagmography facilitates diagnosis of vertigo.